2022
DOI: 10.3390/su142114427
|View full text |Cite
|
Sign up to set email alerts
|

Biological Treatment, Advanced Oxidation and Membrane Separation for Landfill Leachate Treatment: A Review

Abstract: Landfill leachate, especially when produced in old municipal solid waste landfills, is a challenging type of wastewater which contains a variety of toxic substances. The existence of pollutants in the landfill leachate is primarily due to inadequate solid waste separation at the source. Pretreatment on site is a must for the landfill leachate to be safely released into the environment. One-step treatment is insufficient since landfill leachate has a complex composition that spatially and temporally varies. Oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 192 publications
0
2
0
Order By: Relevance
“…Landfill leachate is also a typical type of high-strength wastewater, which has low biodegradability and a high content of COD, nitrogen, and toxic substances [50,51]. Although biological processes are commonly employed for landfill leachate treatment, the refractory organic matters and high ammonia contents are still challenging [51].…”
Section: Landfill Leachatementioning
confidence: 99%
“…Landfill leachate is also a typical type of high-strength wastewater, which has low biodegradability and a high content of COD, nitrogen, and toxic substances [50,51]. Although biological processes are commonly employed for landfill leachate treatment, the refractory organic matters and high ammonia contents are still challenging [51].…”
Section: Landfill Leachatementioning
confidence: 99%
“…One literature review showed that the formation of leachates and their migration in an aquifer, despite the reclamation of old landfills, were serious problems observed in many countries (e.g., the United States of America, China, Italy, and Poland, e.g., [10][11][12][13][14][15]). Despite reclamation, the processes occurring in the stored waste, depending on many complex factors (moisture, temperature, redox conditions, pH, and types of microorganisms), lead to the formation of leachates and biogas, which affect the surrounding environment for a long time [16]. One of many examples is an unlined, closed municipal landfill on the alluvial plain in Norman (Oklahoma, USA), where the leachate plume extends at least 225 m downgradient in the unconfined, 12-meter thick alluvial aquifer [17] with a linear plume velocity of 40.2 m/year [18].…”
Section: Introductionmentioning
confidence: 99%
“…3 Due to the poor pollutant removal effect of traditional biological treatment, the combined process of "physical/chemical treatment" and "biological treatment" is more suitable for deep treatment of late landll leachate. 4 As a powerful advanced oxidation technology, the electrochemical oxidation method has the advantages of versatility, simple operation, no or few chemicals, easy automatic management, no secondary pollution and so on. 5 In recent years, it has received extensive attention in the eld of refractory wastewater, especially for late landll leachate.…”
Section: Introductionmentioning
confidence: 99%